Impact of Borrower Characteristics on Micro Loan Default among Fisheries Sector Evidence from Negombo Sri Lanka - Wathsala, M.G.D.A.; Weerasinghe, W.D.J.D. (Department of Finance, Faculty of Commerce and Management Studies University of Kelaniya Sri Lanka, 2024)
Introduction: This research examines the challenges of the microfinance sector with a focus on the alarming microcredit default rate in the fishing industry in Negombo, Sri Lanka. The study identified the main research problem as high incidence of loan defaults, which negatively affects the growth and sustainability of microfinance institutions. The objective is to explore borrower characteristics that influence microloan default and suggest strategies to reduce microloan default. Methodology: This research follows a quantitative methodology. A structured questionnaire was designed. The questionnaire was collected from 147 microfinance borrowers of Negombo Wallawediya Fishermen's Association through non-probability convenience sampling. SPSS version 23 was used to perform exploratory factor analysis. The findings of this study confirmed six borrower’s factors useful in explaining microfinance loan defaults in Sri Lanka. This research examines the characteristics of microcredit defaulting borrowers in the Negombo fisheries sector. The study focuses on key determinants such as size, gender, income, experience, household size and education level to determine the impact of loan default on the Negombo fisheries sector. Findings: The study found that age, gender, income, experience, household size and education level affect fishermen's late payment. Gender emerges as a critical factor, with women more likely to default on payments than men. Younger borrowers are also more prone to default, suggesting the need for financial education tailored to their needs. Level of education has a modest effect on non-compliance, emphasizing the potential benefits of promoting financial education. Conclusion: Implications suggest further testing and targeted interventions recommendations include social orders and public policies for credit distribution background checks future research proposals include different data collection methods and sustainability approaches limitations of inclusion questions dependent and qualitative methods in future research and reveals a need for regional variations overall the study provides valuable insights and practical recommendations for stakeholders in the microfinance sector.
Keywords: Microloan; Borrowers Characteristics; Loan default; Fisheries sector